Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

a+b=30 ab=25\times 9=225
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 25x^{2}+ax+bx+9. To find a and b, set up a system to be solved.
1,225 3,75 5,45 9,25 15,15
Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 225.
1+225=226 3+75=78 5+45=50 9+25=34 15+15=30
Calculate the sum for each pair.
a=15 b=15
The solution is the pair that gives sum 30.
\left(25x^{2}+15x\right)+\left(15x+9\right)
Rewrite 25x^{2}+30x+9 as \left(25x^{2}+15x\right)+\left(15x+9\right).
5x\left(5x+3\right)+3\left(5x+3\right)
Factor out 5x in the first and 3 in the second group.
\left(5x+3\right)\left(5x+3\right)
Factor out common term 5x+3 by using distributive property.
\left(5x+3\right)^{2}
Rewrite as a binomial square.
x=-\frac{3}{5}
To find equation solution, solve 5x+3=0.
25x^{2}+30x+9=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-30±\sqrt{30^{2}-4\times 25\times 9}}{2\times 25}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 25 for a, 30 for b, and 9 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-30±\sqrt{900-4\times 25\times 9}}{2\times 25}
Square 30.
x=\frac{-30±\sqrt{900-100\times 9}}{2\times 25}
Multiply -4 times 25.
x=\frac{-30±\sqrt{900-900}}{2\times 25}
Multiply -100 times 9.
x=\frac{-30±\sqrt{0}}{2\times 25}
Add 900 to -900.
x=-\frac{30}{2\times 25}
Take the square root of 0.
x=-\frac{30}{50}
Multiply 2 times 25.
x=-\frac{3}{5}
Reduce the fraction \frac{-30}{50} to lowest terms by extracting and canceling out 10.
25x^{2}+30x+9=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
25x^{2}+30x+9-9=-9
Subtract 9 from both sides of the equation.
25x^{2}+30x=-9
Subtracting 9 from itself leaves 0.
\frac{25x^{2}+30x}{25}=-\frac{9}{25}
Divide both sides by 25.
x^{2}+\frac{30}{25}x=-\frac{9}{25}
Dividing by 25 undoes the multiplication by 25.
x^{2}+\frac{6}{5}x=-\frac{9}{25}
Reduce the fraction \frac{30}{25} to lowest terms by extracting and canceling out 5.
x^{2}+\frac{6}{5}x+\left(\frac{3}{5}\right)^{2}=-\frac{9}{25}+\left(\frac{3}{5}\right)^{2}
Divide \frac{6}{5}, the coefficient of the x term, by 2 to get \frac{3}{5}. Then add the square of \frac{3}{5} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{6}{5}x+\frac{9}{25}=\frac{-9+9}{25}
Square \frac{3}{5} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{6}{5}x+\frac{9}{25}=0
Add -\frac{9}{25} to \frac{9}{25} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{3}{5}\right)^{2}=0
Factor x^{2}+\frac{6}{5}x+\frac{9}{25}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{3}{5}\right)^{2}}=\sqrt{0}
Take the square root of both sides of the equation.
x+\frac{3}{5}=0 x+\frac{3}{5}=0
Simplify.
x=-\frac{3}{5} x=-\frac{3}{5}
Subtract \frac{3}{5} from both sides of the equation.
x=-\frac{3}{5}
The equation is now solved. Solutions are the same.